1995
DOI: 10.1002/pro.5560040206
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic potential distribution of the gene V protein from Ff phage facilitates cooperative DNA binding: A model of the GVP‐ssDNA complex

Abstract: The crystal structure of the gene V protein (GVP) from the Ff filamentous phages (M13, f l , fd) has been solved for the wild-type and two mutant (Y41F and Y41H) proteins at high resolution. The Y41H mutant crystal structure revealed crystal packing interactions, which suggested a plausible scheme for constructing the polymeric protein shell of the GVP-single-stranded DNA (ssDNA) complex (Guan Y, et al., 1994, Biochemistry 33:7768-7778). The electrostatic potentials of the isolated and the cooperatively formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…The amount of bound G5P corrected for the bulk contribution is determined as 2702 RU (green line in Figure ), corresponding to an average number of 3.5 G5P molecules, which are directly interacting with each immobilized dT 25 oligonucleotide. This value can be compared with the expected one G5P molecule per four nucleotides, which has been reported in ref for mobile ssDNA in solution. The presence of a 1 M ectoine solution strongly reduces the amount of bound G5P to about one-third of the value obtained in the absence of ectoine.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…The amount of bound G5P corrected for the bulk contribution is determined as 2702 RU (green line in Figure ), corresponding to an average number of 3.5 G5P molecules, which are directly interacting with each immobilized dT 25 oligonucleotide. This value can be compared with the expected one G5P molecule per four nucleotides, which has been reported in ref for mobile ssDNA in solution. The presence of a 1 M ectoine solution strongly reduces the amount of bound G5P to about one-third of the value obtained in the absence of ectoine.…”
Section: Resultssupporting
confidence: 57%
“…In fact, structural studies of G5P 58,63 indicated the presence of highly charged regions which are of specific importance for the binding to DNA. Recent results also indicated a strong decrease of the dielectric constant of water in confined geometries, at interfaces and in electrolyte solutions ?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the number of RFs templated for transcription increases, so too does the number of phage proteins present in the host cell. Late in the infection when the level of pV protein reaches a critical number, it forms dimers and binds at the bottom of the hairpin formed by the packaging signal in the IF DNA and begins to coat the entire length (except the packaging signal) of the DNA, with one antiparallel ssDNA strand bound by each side of the dimer forming a long helical DNA–protein complex containing approximately 1,600 copies of pV . pV also plays a role in timing the infection cycle in the host and coordinating the level of IF for packaging.…”
Section: Filamentous Phage Life Cycle: Genome Replicationmentioning
confidence: 99%
“…Overall, one RF and (+) DNA are newly produced in each cycle from one RF DNA during stage 2. This stage continues until protein V (pV), a phage protein, accumulates to a threshold concentration ( 22 , 25 ). In stage 3, the RF DNA generated in stage 2 continues to replicate itself and generates one (+) strand DNA.…”
Section: Introductionmentioning
confidence: 99%